Features of the modern regionalization of the local self-government system (using the example of thenorthern Caucasus national Republics) - M. V. Limareva (Современная наука и инновации)
In democratic political systems, the question of the quality and effectiveness of the local self-government system has always come first.At the same time, the development of democratic institutions suggested a mutually beneficial dialogue between the authorities and civil society.In countries with a transit system of democracy, where political institutions and civil society are in a state of formation, such dialog forms of relations have always caused numerous complaints due to constant and numerous systemic failures. The North Caucasus region has a number of specific features that are both transformational (modernist) in nature and connected with the historical ethnopolitical traditions existing here. Specificity is largely determined by existing traditions based on the experience of an original pre-state ethnodemocracy, caught up with specific power relations. At the same time, the local government systems existing here are very organically combined with ethnocratic traditions. Up to the analysis of these features this paper would be devoted.